Safety and Efficacy of Distal Perfusion Catheterization to Prevent Limb Ischemia after Common Femoral Artery Cannulation for Extracorporeal Membrane Oxygenation - Chang Ho Jeon; Nak Jong Seong; Chang Jin Yoon (대한영상의학회지, 2016)
Purpose The extracorporeal membrane oxygenation (ECMO) cannula has the potential for obstructing flow to the lower limb, thus causing severe ischemia and possible limb loss. We evaluated the safety and clinical efficacy of percutaneous distal perfusion catheterization in preventing limb ischemia.